Pengaruh pembelajaran melalui media audio visual (Video) terhadap hasil belajar aktivitas ritmik pada Siswa MI Al Abrar Makassar - Juhanis Juhanis; Hasmyati Hasmyati (Seminar Nasional LP2M UNM, 2019)
This research is a kind of quantitative research through an experimental approach of one group pretest-posttest design which aims to find out; The effect of learning through audio visual media (video) on the learning outcomes of rhythmic activity in students of Al Abrar MI Makassar. The population is all students of Al Abrar Makassar MI. The sample used is class III students as many as 30 people. The sampling technique is the Proportion Sampling technique. The data collection technique in this study used a test. The instrument used in this study is a test of the performance of the movement of rhythmic activity. The data analysis technique used t test analysis and previously tested normality and homogeneity through the SPSS 21 program at a significant level of α = 0.05. Based on the analysis of the results of the study and discussion, it can be concluded that: there is a significant effect of learning through audio visual media (video) on the learning outcomes of rhythmic activities of students of Al Abrar Makassar MI with a tcount of -15.397 with a significance value of 0,000 <0.005. The mean value of learning outcomes of the initial rhythmic activity or pre-test was 64.13 while the post-test rose to 79.77